PEMBELAJARAN ONLINE MASA COVID-19 DI PERGURUAN TINGGI (Studi Universitas Muhammadiyah Kotabumi) - Sri Retno Fatimah; Salis M Abduh; M. Ruhly Kesuma Dinata (Universitas Muhammadiyah Kotabumi, 2021)
During the COVID-19 pandemic, it affected the education system which directed the learning system to the implementation of distance learning, so that education continued to work to achieve the functions and objectives of education in Article 3 of Law Number 20 of 2003 concerning the National Education System. The method used in this research is empirical legal research to see directly and observe the objects and circumstances that exist in the research area and their legal effectiveness. A learning policy can be said to be effective and successful if it can realize the functions and objectives of education. The components involved in the learning system such as educators, materials and curriculum, learning methods, infrastructure and learning environments are evaluated to see whether or not the educational functions and objectives are implemented. In online learning during the COVID-19 era, the functions and objectives of education have not been fully achieved due to obstacles in their implementation. The inhibiting factors in its application are lack of concentration, inadequate facilities and infrastructure, limited internet access and limitations in the use of technology. As long as there is no solution to quell the pandemic, online learning must continue and educator practitioners must increase creativity to create quality and interesting learning.